Prevalence of Internet addiction and its association with social support and other related factors among adolescents in China. (October 2016) - Wu, Xiao-Shuang; Zhang, Zhi-Hua; Zhao, Feng; Wang, Wen-Jing; Li, Yi-Feng; Bi, Linda; Qian, Zhen-Zhong; Lu, Shan-Shan; Feng, Fang; Hu, Cai-Yun; Gong, Feng-Feng; Sun, Ye-Huan
Abstract: A cross-sectional study design was applied amongst a random sample (n = 10158) of Chinese adolescents. Self-completed questionnaires, including demographic characteristics, Internet use situation, Youth Internet Addiction Test, Youth Social Support Rating Scale and Zung Self-rating Depression Scale were utilized to examine the study objectives. Among the study population, the prevalence rate of Internet addiction was 10.4%, with 1038 (10.2%) moderately and 21 (0.2%) severely addicted to the Internet. Results from the multivariate logistic regression analyses suggested that a variety of related factors have significant effects on Internet addiction (parental control, per capita annual household income, academic performance, the access to Internet, online activities). The correlation coefficients showed that Internet addiction was negatively correlated with social support and positively associated with depression. Social support had a significant negative predictive effect on Internet addiction. The mediating effect of depression between social support and Internet addiction was remarkable.